Nutritional properties of commercially important cephalopods from the south-west coast of India: Nutritional qualities of cephalopod mollusks - Silpa Kunnappilly Paulose,; Chakraborty, Kajal (Indian Journal of Fisheries, 2024)
Cephalopods are widely regarded as healthy and nutritionally rich seafood resources. This study focuses on analysing the nutritional composition of six commercially important edible cephalopod species viz., Cistopus indicus, Amphioctopus marginatus, Amphioctopus aegina, Sepia pharaonis, Sepia elliptica and Sepia aculeata, from the Malabar coast of the Indian peninsula. The selected cephalopods were determined to be a rich source of protein ranging from 12.41 to 19.02 g 100 g-1. The amino acid profile demonstrated a balanced ratio of essential to non-essential amino acids (0.93-1.63) with a higher concentration of essential amino acids, attributing enhanced biological value of proteins in these cephalopods. S. pharaonis recorded the highest arginine-to-lysine ratio (~1.77), indicating excellent cholesterolemic index. Notably, octopus species had the lowest total cholesterol content (~100 mg 100 g-1) compared to cuttlefish species which recorded higher cholesterol levels (~160 mg 100 g-1). A. marginatus recorded more significant quantities of polyunsaturated fatty acids (PUFA) (36.85% total fatty acids) among all the species studied. Octopus species exhibited significantly greater Σn-3/Σn-6 ratio than cuttlefish species. The ideal atherogenicity/thrombogenicity indices (